2022
DOI: 10.1002/berj.3801
|View full text |Cite
|
Sign up to set email alerts
|

Precarious privilege in the time of pandemic: A hybrid (auto)ethnographic perspective on COVID‐19 and international schooling in China

Abstract: Although the impact of the global COVID‐19 pandemic in terms of school closure and the sudden shift to online learning has started to be explored, little has so far been written about the impact on teachers. This paper addresses this gap by drawing on the first author's autoethnographic experiences of working in the growing body of ‘non‐traditional’ international schooling in Shanghai, China, during the first wave of the pandemic in early 2020. These experiences are complemented by insights from other teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Also, the prevalence of local staff at the schools often with limited experience of higher education internationally may restrict the social capital available to students to guide overseas university applications and offer advice on adapting to higher education abroad. Although not covered in this research, an exodus of expatriate teachers owing to COVID-19 restrictions (see Poole & Bunnell, 2022) may further localise the schools in this respect.…”
Section: Discussionmentioning
confidence: 98%
“…Also, the prevalence of local staff at the schools often with limited experience of higher education internationally may restrict the social capital available to students to guide overseas university applications and offer advice on adapting to higher education abroad. Although not covered in this research, an exodus of expatriate teachers owing to COVID-19 restrictions (see Poole & Bunnell, 2022) may further localise the schools in this respect.…”
Section: Discussionmentioning
confidence: 98%
“…Their pedagogical practices were rationalized and operated within the comfort zone of their cultural frames of reference (Poole, 2019 ). Scholars suggested that foreign teachers from North America and Europe found themselves as a minority when teaching local students in China (Poole & Bunnell, 2022 ). Hence this study targeted the exploration of Western foreign teachers' identities in the Chinese cultural context.…”
Section: Methodsmentioning
confidence: 99%
“…[1] . This period has brought forth challenges [2,3] as well as opportunities [4] for higher educational institutions (HEIs), teaching staff [5,6] , parents [7] , and individual students [8,9] , especially those in vulnerable positions [10] . Beyond the less optimistic aspects, there is another side characterized by resilience and creativity demonstrated by HEI leaders [11] , faculties [12] , and students, leading to the transformation of learning and teaching practices.…”
Section: Introductionmentioning
confidence: 99%
“…While the closure of campuses and the subsequent shift to fully virtual teaching limited physical movement, it also fostered new social dynamics. This includes the emergence of existential (a more authentic self) and spatial (i.e., security) privileges [6] , as well as initiatives to re-shape the education system [2] . Realistically speaking, transformative practices or morphogenesis [13,14] have emerged and are being elaborated in many countries.…”
Section: Introductionmentioning
confidence: 99%